Effects of Euthanasia on Animal Research - Maharani, Ni Putu Radela; Fadlyah, Nur Ashfiya; Setyaningrum, Dyah Ayu Woro; Hairunisa, Nany (Veterinary Biomedical and Clinical Journal, 2024)
The use of experimental animals is widely conducted in the medical field, both for research on the processes of disease occurrence (pathogenesis), the causes of disease (etiology), and research on therapy. Therefore, it is important to understand how euthanasia in experimental animals affects the integrity of the sample and its influence on research results. This article was compiled from several literature sources searched from Google Schoolar and PubMed published within the last 10 years, with keywords such as "code of ethics in experimental animals", "methods of euthanasia in experimental animals", "overdose anesthesia methods in animal euthanasia", "barbiturate injection methods in rats", "inhalation methods in animal euthanasia", "biochemical effects of euthanasia", and "histological effects of euthanasia". This paper discusses euthanasia methods, namely overdose anesthesia, inhalation, and injection. This paper aims to discuss how the method of euthanasia and the choice of drugs can impact the biochemical and histological changes in animals after the euthanasia process. Choosing the right euthanasia method is essential, as the species of animals involved and the research goals are considered. Using methods that align with the biological characteristics and behavior of the animals can help ensure the success of the research while also considering ethical aspects and animal welfare.